Regeneração natural em ecounidades maduras e em reorganização de fragmentos de Floresta Estacional Semidecídua - Sato, Luciane Missae [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The Atlantic Rainforest biome has been going through fragmentation processes caused by agriculture and urbanization in green areas. Structural studies associated with the silvigenetic approach allow the understanding of what the past has caused in the present structure and predict future conditions of disturbed fragments. The objective of this study was to compare the composition and diversity of arboreous natural regeneration of steady-state and reorganization ecounits in two Seasonal Semideciduous Forest fragments. The hypothesis was that specific composition varies in these two different ecounits due to differential adaptation of species in canopy gaps and closed canopy. The survey was made in three areas with different perturbation backgrounds of 0,5 ha each. 60 permanent plots of 4m² each (2m x 2m) were stablished along the studied fragments following the proportion of ecounits presented in a previous mapping. Each plot was divided in 4 sub-plots of 1m² and arboreous individuals between 0,20m and 1,30m height were sampled and posteriorly separated in two height classes: I) individuals between 0,20m and 0,50m height (2m² sampling) and II) individuals between 0,51m and 1,30m height (4m² sampling). It was sampled 338 individuals from 53 families and 23 species. The Shannon index was 3,26 (Area A), 2,27 (Area B) and 2,42 (Area C) whereas Areas B and C values are considered low in our state Semidecidous Forests. Steady-state ecounits presented the highest values for abundance and species richness. Chi-square test pointed out species’ selection for determined ecounits in the studied community. Rarefaction method analysis showed diversity increase in steady-state ecounits and a stablishment in species richness curves for reorganization ecounits

O bioma Mata Atlântica vem sofrendo com o processo de fragmentação causado, principalmente, pela expansão agrícola e urbanização em áreas florestadas. Estudos estruturais associados à abordagem silvigenética permitem entender o que o passado causou na estrutura presente e predizer condições futuras em fragmentos deturpados. O objetivo deste trabalho foi comparar a composição e diversidade da regeneração natural arbórea de ecounidades maduras e em reorganização em dois fragmentos de Floresta Estacional Semidecidual. A hipótese do estudo foi que a composição específica varia entre os tipos de ecounidades em função da adaptação diferencial das espécies a habitats de clareiras e não clareiras. O levantamento foi feito em três áreas amostrais de 0,5 ha cada, com diferentes históricos de perturbação. Foram instaladas parcelas permanentes de 2m x 2m divididas em quatro subparcelas de 1m x 1m, onde foram amostrados indivíduos arbóreos de alturas totais entre 0,20m e 1,30m, separados em duas classes de tamanho: I) de 0,20m até 0,50m (em duas subparcelas, 2m²) e II) 0,51m até 1,30m (na parcela toda, 4m²). Foram encontrados 338 indivíduos distribuídos em 53 famílias e 23 espécies nas três áreas de estudo. O índice de Shannon para cada área foi 3,26 (Área A), 2,27 (Área B) e 2,42 (Área C), sendo os dois últimos valores considerados baixos para Florestas Estacionais Semideciduais do estado. As ecounidades maduras foram os ambientes que apresentaram maiores abundâncias e riquezas de espécies. O teste de chi quadrado apontou preferência de espécies por determinada ecounidade e as análises feitas pelo método de rarefação indicam que há tendência de aumento da diversidade em ecounidades maduras em detrimento das ecounidades em reorganização
Natural regeneration in steady-state and reorganization ecounits of Seasonal Semideciduous Forest fragments
Keywords: Florestas tropicais - Conservação; Desenvolvimento sustentável; Ecologia florestal